Jean Bodin and the Romance of Demonology - McPhail, Eric (Análisis. Revista de investigación filosófica, 2018)
This article proposes a comparison between the French Renaissance demonologist Jean Bodin and the fictional character Don Quijote. Like the hero of Cervantes’ novel, Bodin believes everything he reads. Consequently, Bodin makes his own discipline of demonology a species of romance that eagerly blurs the boundary of fact and fiction. This type of credulity can be usefully juxtaposed to Michel de Montaigne’s understanding of the imagination and to his more philosophical exploration of the realm of possibility. Keywords: Demonology, fiction, imagination, Jean Bodin, Cervantes, Montaigne.